Cesium lead halide perovskite target material and preparation method and application thereof
By simplifying the ball milling, pressing and annealing processes of cesium-lead halogen perovskite targets, combined with magnetron sputtering technology, the problems of complex target preparation and short service life are solved, and uniform film preparation and cost reduction are achieved.
Patent Information
- Application Number
- CN202510772347.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-08-29
AI Technical Summary
The preparation process of existing cesium lead halogen perovskite targets is complex, and there are problems such as short service life and high cost of the target during magnetron sputtering.
The cesium-lead halogen perovskite target is prepared by ball milling, pressing and annealing, and a thin film is prepared on the substrate in combination with magnetron sputtering technology. By optimizing the ball milling speed, pressing pressure and annealing temperature, the preparation process is simplified, and the target service life is extended through glass back targets.
The prepared cesium lead halogen perovskite target has a flat surface and uniform composition distribution. The film has good uniformity after magnetron sputtering, which reduces production costs and extends the service life of the target, and is in line with the concept of energy conservation and environmental protection.
Smart Images

Figure CN120553752A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnetron sputtering, and in particular to a cesium-lead halide perovskite target material and a preparation method and application thereof. Background Art
[0002] Organic-inorganic hybrid perovskites have disadvantages such as poor thermal stability and easy thermal decomposition due to the presence of organic components, which seriously affect the stability and life of optical films. + All-inorganic perovskites (CsPbX3, where X is typically a halogen element such as Cl, Br, or I) not only possess comparable optical properties to hybrid perovskites but also exhibit superior environmental stability. Among common all-inorganic perovskites, CsPbBr3 and CsPbCl3 are more stable than CsPbI3, making them promising materials for optical thin films. Spin coating, blade coating, and slot-slit coating are currently the most commonly used methods for preparing CsPbX3 thin films. However, the low solubility of cesium halide limits the production of dense CsPbX3 films, while spin coating, blade coating, and slot-slit coating methods have limitations when preparing large-area or uniform films. Magnetron sputtering is a well-established thin-film preparation method used in industrial production, capable of producing large-area films with uniform thickness and composition on substrates. Therefore, magnetron sputtering is an ideal method for the low-cost, large-area preparation of perovskite films with uniform composition and thickness.
[0003] The Chinese patent applications for the preparation of perovskite targets and the preparation of perovskite films by magnetron sputtering are as follows: CN112226738A discloses an inorganic cesium lead halide perovskite magnetron sputtering target preparation and recovery and film growth technology, which converts CsX m and PbY n After the powder is ball-milled at -4°C for 4 hours, it is annealed under vacuum conditions. The mixed powder is then poured into a 3-inch pressing mold, pressed using a four-column hydraulic press to obtain a target material, and finally sintered using a muffle furnace. In this process, the ball milling temperature is relatively harsh, and the powder after ball milling needs to be sintered, and the process flow is relatively complicated. In addition, the four-column hydraulic press is slightly insufficient in terms of high-precision pressing. Patent CN111816770A discloses a magnetron sputtering preparation method for perovskite films, which mainly focuses on the application of the perovskite films in solar cell devices; Patent CN106854749A discloses a magnetron sputtering preparation method for perovskite materials and their films, which mainly focuses on the magnetron sputtering preparation of organic-inorganic hybrid perovskite targets and their films; both patents involve the preparation of perovskite targets but do not provide details of the target preparation. At the same time, there is no complete data support, and it is impossible to provide a reference for the preparation of perovskite targets in a true sense. Summary of the Invention
[0004] The purpose of the present invention is to provide a cesium lead halide perovskite target material and its preparation method and application, so as to solve the problem of complex preparation process of cesium lead halide perovskite target material for magnetron sputtering.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a cesium lead halide perovskite target, comprising the following steps: 1) mixing cesium halide and lead halide and then ball milling to obtain a precursor powder; 2) Pressing the precursor powder to obtain a cesium lead halide perovskite target precursor; 3) Annealing the cesium lead halide perovskite target precursor to obtain a cesium lead halide perovskite target.
[0006] Preferably, the cesium halide in step 1) is CsBr or CsCl; The lead halide is PbBr2 or PbCl2; The ball mill has a rotation speed of 200-500 r / min and a time of 3-5 h.
[0007] Preferably, the molar ratio of cesium halide to lead halide in step 1) is 1:0.8-1.2.
[0008] Preferably, the pressing process in step 2) includes pre-pressing and static pressing; The pre-pressing pressure is 20-38 MPa and the time is 2-5 min; The static pressure is 200-300 MPa, the pressurization rate is 5-30 MPa / min, the pressure holding time is 5-10 min, and the pressure relief rate is 5-30 MPa / min.
[0009] Preferably, the annealing temperature in step 3) is 90-150° C., and the annealing time is 8-24 hours; The annealing process is performed in a vacuum environment.
[0010] The present invention provides a cesium-lead halide perovskite target material prepared by the above-mentioned preparation method.
[0011] The present invention provides an application of the above-mentioned cesium lead halide perovskite target in preparing perovskite thin film materials by magnetron sputtering, comprising the following steps: A glass sheet is adhered to the back of a cesium lead halide perovskite target with an adhesive, and then placed in a magnetron sputtering chamber for magnetron sputtering to obtain a cesium lead halide perovskite film on the substrate surface.
[0012] Preferably, the atmosphere of the magnetron sputtering is argon, the gas pressure is 11-12 mTorr, and the gas flow rate is 20-50 sccm; The power of the magnetron sputtering is 20-80W.
[0013] Preferably, the thickness of the prepared cesium lead halide perovskite film is 270~300nm.
[0014] The present invention has at least the following beneficial effects: The preparation method of the cesium lead halide perovskite target disclosed in the present invention is simple, does not require low-temperature ball milling, and does not require high-temperature calcination. The prepared cesium lead halide perovskite target has a smooth surface and uniform composition distribution. It is processed into a perovskite optical film product using magnetron sputtering, which is evenly distributed on the substrate and has good fluorescence properties. Furthermore, the present invention extends the service life of the target by providing a glass back target before magnetron sputtering. The remaining target material after magnetron sputtering is directly ground for recycling, reducing the cost of target production and conforming to the concept of energy conservation and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The XRD characterization diagram of CsPbCl3 powder and CsPbCl3 film in Example 5 is shown in FIG. Figure 1 (a) is the XRD pattern of the CsPbCl3 powder after ball milling and the CsPbCl3 powder after recovery in Example 5. Figure 1 (b) is the XRD pattern of the CsPbCl3 thin film prepared by magnetron sputtering in Example 5; Figure 2 Schematic diagram of the upper and lower surfaces of the pre-pressed block when it is pressed in Example 5; Figure 3 is a SEM image of the CsPbCl3 thin film prepared by magnetron sputtering in Example 5; Figure 4 is the XRD pattern of the precursor powder and the perovskite film in Example 6, Figure 4 (a) is the XRD pattern of the precursor powder prepared in Example 6. Figure 4 (b) is the XRD pattern of the perovskite film prepared in Example 6 before and after annealing; Figure 5 The XRD patterns of the precursor powder and perovskite film prepared in Comparative Example 2 are shown in FIG. Figure 5 (a) is the XRD pattern of the precursor powder prepared in Comparative Example 2. Figure 5 (b) is the XRD pattern of the perovskite film prepared in Comparative Example 2 before and after annealing; Figure 6 The photoluminescence spectra of the perovskite films prepared in Example 6 and Comparative Example 2 are shown. Figure 6 (a) is the photoluminescence spectrum of the perovskite film prepared in Comparative Example 2. Figure 6 (b) is the photoluminescence spectrum of the perovskite film prepared in Example 6; Figure 7 The XRD pattern of the target powder obtained by recycling the perovskite target prepared in Example 6 for each of the three times; Figure 8 XRD patterns of the perovskite film prepared by initial sputtering of the perovskite target prepared in Example 6 and the perovskite film prepared after continuous sputtering for 13 hours. DETAILED DESCRIPTION
[0016] The present invention provides a method for preparing a cesium lead halide perovskite target, comprising the following steps: 1) mixing cesium halide and lead halide and then ball milling to obtain a precursor powder; 2) Pressing the precursor powder to obtain a cesium lead halide perovskite target precursor; 3) Annealing the cesium lead halide perovskite target precursor to obtain a cesium lead halide perovskite target.
[0017] In the present invention, the cesium halide in step 1) is CsBr or CsCl, and the lead halide is PbBr2 or PbCl2.
[0018] In the present invention, the purity of the cesium halide and lead halide is analytically pure or above.
[0019] In the present invention, the ball mill has a rotation speed of 200-500 r / min, preferably 250-450 r / min, more preferably 300-400 r / min, and more preferably 300 r / min; and a ball milling time of 3-5 h, preferably 3-4.5 h, and more preferably 3-3.5 h.
[0020] In the present invention, the molar ratio of cesium halide to lead halide in step 1) is 1:0.8-1.2, and can be selected from 1:0.8, 1:0.9, 1:1, 1:1.1, and 1:1.2.
[0021] In the present invention, when the cesium halide and the lead halide in step 1) are CsBr and PbBr2, the molar ratio of the two is preferably 1:1.2.
[0022] In the present invention, when the cesium halide and the lead halide in step 1) are CsCl and PbCl2, the molar ratio between the two is preferably 1:1.
[0023] In the present invention, the pressing process in step 2) includes pre-pressing and static pressing.
[0024] In the present invention, the pre-pressing pressure is 20-38 MPa, preferably 22-38 MPa, more preferably 25-38 MPa, and more preferably 38 MPa; the pre-pressing time is 2-5 min, preferably 3-5 min, and more preferably 5 min.
[0025] In the present invention, the static pressure is 200~300MPa, preferably 220~280MPa, more preferably 240~260MPa, and more preferably 250MPa; the pressurization rate is 5~30MPa / min, preferably 10~25MPa / min, and more preferably 15~20MPa / min; the holding time is 5~10min, preferably 6~10min, and more preferably 10min; the pressure release rate is 5~30MPa / min, preferably 10~25MPa / min, and more preferably 15~20MPa / min.
[0026] In the present invention, the annealing temperature in step 3) is 90-150°C, preferably 100-140°C, more preferably 110-130°C, and more preferably 130°C; the annealing time is 8-24h, preferably 10-22h, more preferably 12-20h, and more preferably 12-15h.
[0027] In the present invention, the environment of the annealing treatment is a vacuum environment.
[0028] The present invention provides a cesium-lead halide perovskite target material prepared by the above-mentioned preparation method.
[0029] The present invention provides an application of the above-mentioned cesium lead halide perovskite target in preparing perovskite thin film materials by magnetron sputtering, comprising the following steps: In the present invention, a glass sheet is adhered to the back of a cesium lead halide perovskite target material using an adhesive, and then placed in a magnetron sputtering chamber for magnetron sputtering to obtain a cesium lead halide perovskite thin film on the substrate surface.
[0030] In the present invention, the atmosphere of the magnetron sputtering is argon, the gas pressure is 11~12mTorr, preferably 11.2~11.8mTorr, more preferably 11.4~11.6mTorr, more preferably 11.5mTorr; the gas flow rate is 20~50sccm, preferably 25~48sccm, more preferably 30~45sccm, more preferably 35~42sccm.
[0031] In the present invention, the power of the magnetron sputtering is 20-80 W, preferably 20-70 W, more preferably 20-60 W, and even more preferably 20-50 W.
[0032] In the present invention, the thickness of the cesium lead halide perovskite film is 270-300 nm, preferably 275-295 nm, more preferably 280-290 nm, and even more preferably 285 nm.
[0033] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0034] Example 1 (1) Cesium chloride and lead chloride were mixed in a molar ratio of 1:1 and ball milled to prepare CsPbCl3 precursor powder. Zirconia balls of different particle sizes (2mm, 4mm, 5mm, and 6mm balls in a ratio of 3:2:1:1) were added during the ball milling process. The ball mill speed was 300 r / min and the ball milling was carried out for 3 hours. During this process, the ball mill rotated forward for 5 minutes, paused for 1 minute, and then ran in the reverse direction for 5 minutes. This constituted one cycle, and a total of 18 cycles were performed. After the ball milling was completed, the precursor powder was sieved through a 200-mesh sieve and then entered the next step.
[0035] (2) 65 g of precursor powder was placed into a 3-inch pressing mold, the pressing pressure was set to 20 MPa, the holding time was 2 min, and a pre-pressed block was obtained after the pressing was completed. The diameter of the pre-pressed block was 7.62 cm and the thickness was 4 mm.
[0036] The pre-pressed block is sealed and placed in a cold isostatic pressing device, which uses a step-by-step pressurization and pressure relief process for pressing: the pressurization rate is 15 MPa / min. When the pressure rises to 200 MPa, the pressure is maintained for 5 minutes, and then the pressure is released at a rate of 15 MPa / min. Finally, the perovskite target precursor is formed by pressing with a diameter of 7 cm and a thickness of 3.5 mm.
[0037] (3) The perovskite target precursor was placed in a vacuum environment at 130°C for 12 hours to obtain a cesium lead chloride perovskite target.
[0038] Example 2 (1) Cesium chloride and lead chloride were mixed in a molar ratio of 1:1 and ball milled to prepare CsPbCl3 precursor powder. Zirconia ball milling beads of different particle sizes (2mm, 4mm, 5mm, and 6mm in a ratio of 3:2:1:1) were added during the ball milling process. The ball mill speed was 300r / min and the ball milling was carried out for a total of 3h. During this process, the ball mill rotated forward for 5min, paused for 1min, and then ran in the reverse direction for 5min. This constituted one cycle. A total of 18 cycles were performed to obtain the precursor powder. After the ball milling was completed, the precursor powder was sieved through a 200-mesh sieve and then entered the next step.
[0039] (2) 60 g of precursor powder was placed into a 3-inch pressing mold, the pressing pressure was set to 20 MPa, the holding time was 2 min, and a pre-pressed block was obtained after the pressing was completed. The diameter of the pre-pressed block was 7.62 cm and the thickness was 3.5 mm.
[0040] The pre-pressed block is sealed and placed in a cold isostatic pressing device, which uses a step-by-step pressurization and pressure relief process for pressing: the pressurization rate is 15 MPa / min. When the pressure rises to 200 MPa, the pressure is maintained for 5 minutes, and then the pressure is released at a rate of 15 MPa / min. Finally, the perovskite target precursor is pressed and formed, with a diameter of 7.1 cm and a thickness of 3 mm.
[0041] (3) The perovskite target precursor was placed in a vacuum environment at 130°C for 12 hours to obtain a cesium lead chloride perovskite target.
[0042] Example 3 (1) Cesium chloride and lead chloride were mixed in a molar ratio of 1:1 and ball milled to prepare CsPbCl3 precursor powder. Zirconia ball milling beads of different particle sizes (2mm, 4mm, 5mm, and 6mm in a ratio of 3:2:1:1) were added during the ball milling process. The ball mill speed was 300r / min and the ball milling was carried out for a total of 3h. During this process, the ball mill rotated forward for 5min, paused for 1min, and then ran in the reverse direction for 5min. This constituted one cycle. A total of 18 cycles were performed to obtain the precursor powder. After the ball milling was completed, the precursor powder was sieved through a 200-mesh sieve and then entered the next step.
[0043] (2) 60 g of precursor powder was placed into a 3-inch pressing mold, the pressing pressure was set to 35 MPa, the holding time was 5 min, and a pre-pressed block was obtained after the pressing was completed. The diameter of the pre-pressed block was 7.62 cm and the thickness was 3 mm.
[0044] The pre-pressed block is sealed and placed in a cold isostatic pressing device, which uses a step-by-step pressurization and pressure relief process for pressing: the pressurization rate is 15 MPa / min. When the pressure rises to 200 MPa, the pressure is maintained for 5 minutes, and then the pressure is released at a rate of 15 MPa / min. Finally, the perovskite target precursor is obtained by pressing and forming with a diameter of 7.4 cm and a thickness of 3 mm.
[0045] (3) The perovskite target precursor was placed in a vacuum environment at 130°C for 12 hours to obtain a cesium lead chloride perovskite target.
[0046] Example 4 (1) Cesium chloride and lead chloride were mixed in a molar ratio of 1:1 and ball milled to prepare CsPbCl3 precursor powder. Zirconia ball milling beads of different particle sizes (2mm, 4mm, 5mm, and 6mm in a ratio of 3:2:1:1) were added during the ball milling process. The ball mill speed was 300r / min and the ball milling was carried out for a total of 3h. During this process, the ball mill rotated forward for 5min, paused for 1min, and then ran in the reverse direction for 5min. This constituted one cycle. A total of 18 cycles were performed to obtain the precursor powder. After the ball milling was completed, the precursor powder was sieved through a 200-mesh sieve and then entered the next step.
[0047] (2) 60 g of precursor powder was placed into a 3-inch pressing mold, the pressing pressure was set to 38 MPa, the holding time was 5 min, and a pre-pressed block was obtained after the pressing was completed. The diameter of the pre-pressed block was 7.62 cm and the thickness was 3 mm.
[0048] The pre-pressed block is sealed and placed in a cold isostatic pressing device, which uses a step-by-step pressurization and pressure relief process for pressing: the pressurization rate is 15 MPa / min. When the pressure rises to 200 MPa, the pressure is maintained for 5 minutes, and then the pressure is released at a rate of 15 MPa / min. Finally, the perovskite target precursor is pressed and formed, with a diameter of 7.5 cm and a thickness of 3 mm.
[0049] (3) The perovskite target precursor was placed in a vacuum environment at 130°C for 12 hours to obtain a cesium lead chloride perovskite target.
[0050] Example 5 (1) Cesium chloride and lead chloride were mixed in a molar ratio of 1:1 and CsPbCl3 precursor powder was prepared by ball milling. During the ball milling process, zirconium oxide ball milling beads of different particle sizes (2mm, 4mm, 5mm, 6mm ball milling beads in a ratio of 3:2:1:1) were added for mixed ball milling. The ball mill speed was 300r / min and the ball milling was carried out for a total of 3h. In this process, the ball mill rotated forward for 5min, paused for 1min, and then ran in the reverse direction for 5min. This was one cycle. A total of 18 cycles were performed to obtain the precursor powder. After the ball milling was completed, the precursor powder was sieved through a 200-mesh sieve and subjected to X-ray diffraction (XRD) test, as shown in FIG. Figure 1 As shown in (a), the diffraction peaks in the spectrum match well with the standard PDF card, and no obvious impurity peaks are detected, indicating that CsPbCl3 perovskite material has been generated by ball milling the precursor powder.
[0051] (2) 60 g of precursor powder was placed into a 3-inch pressing mold, the pressing pressure was set to 38 MPa, the holding time was 5 min, and a pre-pressed block was obtained after the pressing was completed. The diameter of the pre-pressed block was 7.62 cm and the thickness was 3 mm.
[0052] The pre-pressed block is sealed and placed in a cold isostatic pressing device, which uses a step-by-step pressurization and pressure relief process for pressing: the pressurization rate is 15MPa / min, and when the pressure rises to 250MPa, the pressure is maintained for 10 minutes, and then the pressure is released at a rate of 15MPa / min. Finally, the perovskite target precursor is pressed and formed, with a diameter of 7.4cm and a thickness of 3.5mm. During the static pressing process, a disc with a larger diameter than the pre-pressed block is fixed on the upper and lower surfaces of the pre-pressed block, such as Figure 2 As shown, the target material can be effectively prevented from being deformed due to high pressure in the cold isostatic pressing equipment.
[0053] (3) The perovskite target precursor was placed in a vacuum environment at 130°C for 12 hours to obtain a cesium lead chloride perovskite target.
[0054] A glass wafer was attached to the back of the perovskite target prepared in this example, and then placed in a magnetron sputtering chamber. Sputtering was carried out in an argon atmosphere of 11 mTorr, with an argon flow rate of 42 sccm and a sputtering power of 20 W for 3 hours, ultimately obtaining a CsPbCl3 perovskite film with a thickness of 300 nm. The film was annealed at 130°C under vacuum for 1 hour and then subjected to XRD testing. The XRD pattern is shown in Figure 2. Figure 1 As shown in (b), the diffraction peaks are in good agreement with the standard PDF card, indicating that the target prepared by sputtering successfully obtained the CsPbCl3 perovskite film. Scanning electron microscopy (SEM) results show that the film is evenly distributed on the substrate, as shown in Figure 2. Figure 3 shown.
[0055] The surface of the target material is cracked after use. The target material surface is polished clean with sandpaper, and then the target material is crushed and ground into powder with a mortar to achieve target powder recovery. The XRD test structure of the recycled CsPbCl3 perovskite powder is as follows: Figure 1 As shown in (a) in Figure 1 It can be seen from (a) that the powder obtained after grinding the recycled target material is still CsPbCl3, which means that the recycled material can be reused, reducing the production cost of the target material.
[0056] Example 6 Cesium bromide and lead bromide were mixed in a molar ratio of 1:1.2, and CsPbBr3 powder was prepared by ball milling. During the ball milling process, zirconium oxide ball milling beads of different particle sizes (2mm, 4mm, 5mm, 6mm ball milling beads in a ratio of 3:2:1:1) were added for mixed ball milling. The ball mill speed was 300r / min, and the ball milling was carried out for a total of 3 hours. In this process, the ball mill rotated forward for 5 minutes, paused for 1 minute, and then ran in the reverse direction for 5 minutes. This was one cycle, and a total of 18 cycles were performed. After the ball milling was completed, the powder was sieved through a 200-mesh sieve to obtain a precursor powder, and the precursor powder was subjected to XRD testing. The test results are shown as follows: Figure 4 As shown in (a), the precursor powder is a mixed phase of CsPb2Br5 and CsPbBr3.
[0057] During the pre-pressing process, 50 g of powder was first loaded into a 3-inch pressing mold, the pressing pressure was set to 38 MPa, the holding time was 5 minutes, and the pre-pressed block was obtained after the pressing was completed.
[0058] The pre-pressed block was sealed with discs fixed to its upper and lower surfaces and placed in a cold isostatic press. The pressurization and depressurization were performed in a stepped manner at a rate of 15 MPa / min. When the pressure reached 250 MPa, it was maintained for 10 minutes before being released at a rate of 15 MPa / min. This resulted in a target with a diameter of 7.6 cm.
[0059] After the target material is pressed, it is placed in a vacuum environment at 130°C for 12 hours of annealing.
[0060] Before magnetron sputtering, a circular glass back target of the same size as the target was fixed to the back of the target using high-temperature resistant adhesive. The assembled target was placed in a magnetron sputtering chamber and sputtered onto the substrate in an argon atmosphere at 11 mTorr with a flow rate of 42 sccm and a sputtering power of 20 W for 5 hours. A 270 nm thick film was obtained and subjected to XRD analysis. The film was then annealed at 130°C under vacuum for 1 hour and subjected to XRD analysis again. Figure 4 (b) shows the XRD test patterns before and after film annealing. It can be seen that the sputtered film is a pure CsPbBr3 phase, and the diffraction peak intensity of the CsPbBr3 perovskite film is significantly enhanced after annealing. The intensity of the main diffraction peak increases by about 10 times, the peak shape becomes sharper, and the half-height width decreases by about 50%, indicating that annealing treatment has an improving effect on the crystallization quality of the film. Figure 6 (b) is a photoluminescence (PL) spectrum of the perovskite film prepared in this example, which shows that the film has a fluorescence peak corresponding to the CsPbBr3 band edge emission at 518.49 nm.
[0061] The target material was recycled three times, and the corresponding powder was taken for XRD test each time. Figure 7 As shown in the figure: after three recyclings, the composition of the target powder recycled each time is the same. Therefore, the recycled perovskite powder can still be used, which greatly reduces the production cost of the target material.
[0062] The experimental results show that the perovskite target equipped with a glass back target exhibits excellent durability during the sputtering process, and its service life can support a cumulative sputtering of at least 13 hours. Figure 8 The XRD patterns of a film prepared using a new target and an old target after 13 hours of cumulative sputtering in Example 6 are shown. The diffraction peak positions remain unchanged, but the intensities differ. The diffraction peak intensity of the perovskite film prepared using the old target after 13 hours of cumulative sputtering is significantly weakened, indicating deterioration in the film's crystal quality. However, the film remains pure CsPbBr3, with no phase transition occurring.
[0063] Comparative Example 1 (1) Cesium chloride and lead chloride were mixed in a molar ratio of 1:1 and CsPbC was prepared by ball milling. l3 Precursor powder. During ball milling, zirconia beads of different particle sizes (2mm, 4mm, 5mm, and 6mm in a ratio of 3:2:1:1) were added and mixed. The mill speed was 300 rpm for 3 hours. During this process, the ball mill rotated forward for 5 minutes, paused for 1 minute, and then reversed for 5 minutes. This cycle was repeated 18 times to obtain the precursor powder. After ball milling, the precursor powder was sieved through a 200-mesh screen before proceeding to the next step.
[0064] (2) 60 g of precursor powder was placed into a 3-inch pressing mold, the pressing pressure was set to 38 MPa, the holding time was 5 min, and a pre-pressed block was obtained after the pressing was completed. The diameter of the pre-pressed block was 7.62 cm and the thickness was 3 mm.
[0065] After the pre-pressed block is sealed, it is placed in a cold isostatic pressing device, which uses a stepped pressurization and pressure relief process for pressing: the pressurization rate is 15MPa / min, and when the pressure rises to 300MPa, the pressure is maintained for 10min, and then the pressure is released at a rate of 15MPa / min. The perovskite target precursor finally obtained is severely distorted and unformed. It can be seen from Examples 1 to 5 and Comparative Example 1 that the amount of precursor powder, pre-pressing pressure and holding time, static pressure and holding time will have a significant effect on the size of the target. The greater the powder mass, the greater the pressure, and the longer the holding time, the greater the degree of shrinkage of the target size obtained. In addition, under the action of a relatively high pressure, the target will be severely deformed after being pressed.
[0066] Comparative Example 2 Cesium bromide and lead bromide were mixed in a molar ratio of 1:1, and CsPbBr3 precursor powder was prepared by ball milling. During the ball milling process, zirconium oxide ball milling beads of different particle sizes (2mm, 4mm, 5mm, 6mm ball milling beads in a ratio of 3:2:1:1) were added for mixed ball milling. The ball mill speed was 300r / min, and the ball milling was carried out for a total of 3h. In this process, the ball mill rotated forward for 5min, paused for 1min, and then ran in the reverse direction for 5min. This was one cycle, and a total of 18 cycles were performed. After the ball milling was completed, the powder was sieved through a 200-mesh sieve and subjected to XRD testing, as shown in FIG. Figure 5 As shown in (a), after 3 h of ball milling, the powders have been mixed evenly and CsPbBr3 perovskite material has been generated.
[0067] During the pre-pressing process, 50 g of powder was first loaded into a 3-inch pressing mold, the pressing pressure was set to 38 MPa, the holding time was 5 minutes, and the pre-pressed block was obtained after the pressing was completed.
[0068] The pre-pressed block was sealed with discs fixed to its upper and lower surfaces and placed in a cold isostatic press. The pressurization and depressurization were performed in a stepped manner at a rate of 15 MPa / min. When the pressure reached 250 MPa, it was maintained for 10 minutes before being released at a rate of 15 MPa / min. This resulted in a target with a diameter of 7.6 cm.
[0069] After the target material is pressed, it is placed in a vacuum environment at 130°C for 12 hours of annealing.
[0070] Before sputtering, a glass back target was first fixed to the back of the target material using high-temperature resistant glue. The assembled target material was then placed in a magnetron sputtering chamber and sputtered onto the substrate in an argon atmosphere of 11mTorr with an argon flow rate of 42sccm and a sputtering power of 20W for 3 hours. A film with a thickness of 270nm was finally obtained and subjected to XRD testing. The film was then annealed under vacuum conditions at 130°C for 1 hour and XRD testing was performed again. Figure 5 (b) is the XRD test spectrum before and after film annealing. It can be seen that the sputtered film is a mixed phase of Cs4PbBr6 and CsPbBr3, and annealing has no obvious effect on improving the crystallization quality of the film. Figure 6 (a) is a photoluminescence spectrum of the thin film prepared in this example after annealing treatment, which shows that the film has a fluorescence peak corresponding to the CsPbBr3 band edge emission at 515.61nm.
[0071] Therefore, the mixing ratio of the two precursor powders, CsBr and PbBr2, during ball milling will also affect the composition and quality of the film. The present invention obtains a pure CsPbBr3 film by adjusting the mixing ratio of the precursor powders.
[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a cesium lead halide perovskite target, characterized in that: The following steps are involved: 1) mixing cesium halide and lead halide and then ball milling to obtain a precursor powder; 2) Pressing the precursor powder to obtain a cesium lead halide perovskite target precursor; 3) Annealing the cesium lead halide perovskite target precursor to obtain a cesium lead halide perovskite target.
2. The method for preparing a cesium lead halide perovskite target according to claim 1, wherein: The cesium halide in step 1) is CsBr or CsCl; The lead halide is PbBr2 or PbCl2; The ball mill has a rotation speed of 200-500 r / min and a time of 3-5 h.
3. The method for preparing a cesium lead halide perovskite target according to claim 2, wherein: The molar ratio of cesium halide to lead halide in step 1) is 1:0.8-1.
2.
4. The method for preparing a cesium lead halide perovskite target according to any one of claims 1 to 3, wherein: The pressing process in step 2) includes pre-pressing and static pressing; The pre-pressing pressure is 20-38 MPa and the time is 2-5 min; The static pressure is 200-300 MPa, the pressurization rate is 5-30 MPa / min, the pressure holding time is 5-10 min, and the pressure relief rate is 5-30 MPa / min.
5. The method for preparing a cesium lead halide perovskite target according to claim 4, wherein: The annealing temperature in step 3) is 90-150° C., and the annealing time is 8-24 hours; The annealing process is performed in a vacuum environment.
6. A cesium lead halide perovskite target material prepared by the method for preparing a cesium lead halide perovskite target material according to any one of claims 1 to 5.
7. Use of the cesium lead halide perovskite target material according to claim 6 in preparing perovskite thin film materials by magnetron sputtering, characterized in that: The following steps are involved: A glass sheet is adhered to the back of a cesium lead halide perovskite target, which is then placed in a magnetron sputtering chamber for magnetron sputtering to obtain a cesium lead halide perovskite film on the substrate surface.
8. Use of the cesium lead halide perovskite target according to claim 7 in preparing perovskite thin film materials by magnetron sputtering, characterized in that: The magnetron sputtering atmosphere is argon, the gas pressure is 11-12 mTorr, and the gas flow rate is 20-50 sccm; The power of the magnetron sputtering is 20-80W.
9. Use of the cesium lead halide perovskite target according to claim 8 in preparing perovskite thin film materials by magnetron sputtering, characterized in that: The thickness of the cesium lead halide perovskite film is 270-300 nm.
Citation Information
Patent Citations
Preparation method of perovskite material and relevant film thereof
CN106854749A
Preparation method of perovskite thin film, perovskite thin film, and solar cell device using perovskite thin film and magnetron sputtering instrument
CN111816770A
Inorganic cesium-lead halide perovskite magnetron sputtering target material preparation and recovery and film growth technology
CN112226738A
Cited By
Perovskite heterojunction and preparation method and application thereof
CN122466402A
